PENGARUH KURIKULUM 2013, KEMAMPUAN PENDIDIK DAN SARANA PRASARANA TERHADAP MUTU PENDIDIKAN SMK NEGERI 2 BOJONEGORO - jurnalmap map; Itut Kartika Dewi; Mei Indrawati; Cathrine Sri Hartati (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
ABSTRACT This study aims to find and describe the condition of the 2013 curriculum, educator's ability, educational facilities and infrastructure at SMK Negeri 2 Bojonegoro. To test and analyze curriculum variables, educators and facilities either partially or simultaneously to the quality of education in SMK Negeri 2 Bojonegoro. The number of population in this research is all teachers of SMK Negeri 2 Bojonegoro which guilty 37 people. In this research the analysis technique used is simple linear regression with the help of tool using SPSS program. The results of the 2013 curriculum data analysis, the ability of educators and practical facilities in general and simultaneously for education at SMK Negeri 2 Bojonegoro. Keywords: curriculum 2013, educator's ability, facilities, and quality of education